TRANSLATING AYAHS ALEUDUL العدول IN THE QURANIC CONTEXTS: AN INTERDISCIPLINARY JURISPRUDENTIAL LINGUISTIC STUDY - Alhaj, Ali Albashir Mohammed (QiST: Journal of Quran and Tafseer Studies, 2024)
The current research paper aims to critically study translating Ayahs Aleudul العدول in the Quranic contexts from an interdisciplinary jurisprudential linguistic perspective. The findings of the study showed that Aleudul العدول in the Qur'anic context is a phenomenon that reoccurs in many ayahs. The researcher selected one of the many: the Quranic Arabic Aleudul العدول in Ayah 33 of Surat al-Ahzab to explain the phenomenon and discuss it in detail. The study also showed that the Quranic Arabic Aleudul العدول came in the Qur'anic context to reveal the importance of the meaning to be explained in the context to which it is assigned. The foremost of the problems encountered by translators of the Holy Quran was the dearth of most exegesis relating to this recurring phenomenon in the Holy Qur'an. This is because exegesis is founded on the segmentation of the ayahs rather than a single ayah to determine their denotations and memorize the rulings from them only once.